DIAGNOSIS DAN TATALAKSANA CEDERA MEDULA SPINALIS TRAUMATIK - Andika Surya Atmadja; Sekplin A. S. Sekeon; Denny J. Ngantung (Neurologi Manado, 2021)
Traumatic spinal cord injury is a trauma that affect spinal cord and or another structures around it that made temporary or permanent changes in motoric, sensory and or autonomic function. Around 15% patient with traumatic head injury also had spinal cord injury (SCI). Also, around 25% patient with SCI also had head injury. Around 55% SCI occur in cervical, 15% in thoracal, 15% in thoracolumbal, and 15% in thoracosacral. It have to be remembered that SCI could occur multiple. Around 10% patient with fracture in vertebrae cervical also had vertebral fracture in another segment. Management in SCI should be started from the accident place. It needs a right immobilization and transfer technique. Around 3-25% SCI happen after the first trauma, like in the first management or transportation. SCI patient need imaging. The Joint Section on Disorder of the Spine and Peripheral Nerves of the American Association of Neurological Surgeons and the Congress of Neurological Surgeons divide the patient’s condition into 3 categories, the patient without symptom and fully alert, patient with symptom and fully alert, and unconscious patient. This imaging decision is based on National Emergency X-Radiography Utilization Study Group (NEXUS). The usage methylprednisolone according to NASCIS had some controversies. Operative treatment is aimed to decompression, repair the deformity, and stabilize the vertebrae. In acute phase, operation aim to reduce compression in spinal cord and ischemic so it could make an optimal condition for neurological restoration.